The use of adhesive in Malaysia / Rinawati Mohd Yusof - Mohd Yusof, Rinawati (2002)
The using of adhesive is important in wood industry for our country. It using widely for product with wood such as panel, furniture, construction and etc. The choosing of suitable adhesive must be the important criteria to make sure the usage are effective. Economical using of adhesive is important to decrease or minimize the company operating cost without affecting the quality in the wood industry.